(untitled) - Cunningham, William P. (New York, 2012)
Environmental Science A Global Concern Twelfth Edition is a comprehensive presentation of environmental science for nonscience majors which emphasizes critical thinking environmental responsibility and global awareness; This book is intended for use in a one or twosemester course in environmental science human ecology or environmental studies at the college or advanced placement high school level.
Keywords: Environmental sciences,Khoa học môi trường